Technology as an Elixir to the Future of Education: Impact on the Traditional Modes of Teaching - Severine Pinto; A. Lourdusamy (International Journal of Case Studies in Business, IT and Education (IJCSBE), 2021)
Purpose: In the globally competitive 21st century, one has to be technically literate, able to use technology with much ease. Technology has revolutionized the field of education while automating manual tasks. With the implementation of computers, the task of the teachers is made easier not only in the process of imparting knowledge, but also in the grading and assessment process. As education is a process of social development, there is always a platform to bring about change through educational reforms like curriculum pedagogy, online or digital education, compulsory and high-quality education along with organizing learning programme for teachers that are considered essential and are prioritized with the support of the government. And without doubts its implementation leads to greater effectiveness and efficiency. Technology is an elixir that connects parents and guardians with educational institutions. In this process, innovative pedagogy is implemented with the redesigning of the classrooms. This paper aims to explore the discrepancies causing hurdles in the effective imparting of knowledge through online instruction. The implication of the research conducted focuses on identifying and labelling positive and negative factors, that is not a prominent part of the mainstream mechanism of education but have a draconian impact on it. Design/Methodology/Approach: The researcher conducted a survey with a designed questionnaire seeking feedback from teachers about their online mode experience during the COVID 19 pandemic. Findings/Result: Teachers lack the necessary training and tools to effectively deliver lectures. Social backgrounds, home environment, mental wellbeing, inaccessibility with regard to materials and methodologies also poses a problem. Originality/Value: Based on the survey conducted it is argued that there is a need of a hand-holding mentor facilitating self-motivation in students. Students lack time management skills, ability to use their potentials, think on their own, develop personal and interpersonal skills to solve difficult, challenging problems and collude effectively. Paper Type: It’s empirical research.